Revisiting positionality through intersectional identities: A retrospective of parent and child research. Issue 3 (17th October 2022) - Kabuto, Bobbie
Abstract: Parent and child research has made important contributions to literacy research and advanced research methodologies in studying linguistically diverse families. Positionality has been a cornerstone concept in ethnographic research and often referenced in parent and child studies. In this article, I present a review of the literature on parent and child research published between 2010 and 2021 to explore matters of positionality. The data consist of 24 articles in peer‐reviewed journals, which were analyzed through a content analysis to investigate the diverse ways that parents and children were co‐positioned within a research context through the lens of intersectional identities. Findings specifically focus on nine of the 24 studies that address linguistic diversity in language and literacy learning. This article will conclude with recommendations for addressing positionality within parent and child research processes.